Inventory of Mango Diversity (Mangifera L.) in Bengkulu Province - Fitmawati (International Journal of Ecophysiology, 2020)
Mango (Mangifera L.) is a horticulture crop that grows in tropical regionthat has high diversity in Bengkulu Province. However, its diversity in this province has not been revealed, whereas on the other hand mango diversity is currently endangered due to the conversion of forests from natural habitat to plantation and industry. This study was aimed to determine the mango diversity in Bengkulu using morphological characters. All of the speciemens were collected from the field using exploration method that conducted from September 2016 to March 2017. A total of 17 individuals of mango were examined, and classified into seven mango species. The examination was conducted on the morphological characters, these characters were then scored and analyzed using NTSYSpc 2.02. The coefficient of similarity of 17 mango trees ranges from 0.45 to 0.80. Dendrogram showed that the clustering of mango was not based on the origin of the population but based on the morphological characters. The first group comprises six individuals and the second group consists of 11 individuals